Comparison of observed and modeled seasonal crustal vertical displacements derived from multi‐institution GPS and GRACE solutions. Issue 14 (30th July 2017) - Gu, Yanchao; Fan, Dongming; You, Wei
Abstract: Eleven GPS crustal vertical displacement (CVD) solutions for 110 IGS08/IGS14 core stations provided by the International Global Navigation Satellite Systems Service Analysis Centers are compared with seven Gravity Recovery and Climate Experiment (GRACE)‐modeled CVD solutions. The results of the internal comparison of the GPS solutions from multiple institutions imply large uncertainty in the GPS postprocessing. There is also evidence that GRACE solutions from both different institutions and different processing approaches (mascon and traditional spherical harmonic coefficients) show similar results, suggesting that GRACE can provide CVD results of good internal consistency. When the uncertainty of the GPS data is accounted for, the GRACE data can explain as much as 50% of the actual signals and more than 80% of the GPS annual signals. Our study strongly indicates that GRACE data have great potential to correct the nontidal loading in GPS time series. Key Points: High internal consistency among crustal vertical displacements derived from GRACE Large uncertainty in the vertical components among IGS Analysis Center time series solutions Significant ability of GRACE data to explain the nontidal effects in GPS observations